Crystal structure of the GluR2 amino-terminal domain provides insights into the architecture and assembly of ionotropic glutamate receptors. - Clayton, A; Siebold, C; Gilbert, R; Sutton, G; Harlos, K; McIlhinney, R; Jones, E; Aricescu, A (2009)
Ionotropic glutamate receptors are functionally diverse but have a common architecture, including the 400-residue amino-terminal domain (ATD). We report a 1.8-A resolution crystal structure of human GluR2-ATD. This dimeric structure provides a mechanism for how the ATDs can drive receptor assembly and subtype-restricted composition. Lattice contacts in a 4.1-A resolution crystal form reveal a tetrameric (dimer-dimer) arrangement consistent with previous cellular and cryo-electron microscopic data for full-length AMPA receptors.